Maternity validation using sire‐only BovineSNP50 BeadChip data. (31st May 2013) - Seroussi, E.; Glick, G.; Shirak, A.; Ezra, E.; Zeron, Y.; Ron, M.; Weller, J. I.
Summary: Based on pairwise identity‐by‐state (IBS) distances and whole‐genome SNP data, kinship was investigated in the Israeli Holstein population. A total of 789 bulls, including most of the artificial insemination sires in service since 1987, were genotyped by the BovineSNP50 BeadChip. This sample included up to five generations. For each bull‐by‐bull combination, three states are possible for each marker: no match, a single match and both alleles match. Summing over all markers, the 932 598 IBS scores (three match frequencies*310 866 bull‐by‐bull combinations) were visualized using three‐dimensional coordinates that corresponded to the frequencies of the three possible states. Results were reduced to two dimensions using the transformations x' = 0.7071(1 + freq1−freq2) and y' = 1.2247freq0. Bull‐by‐bull pairs were grouped according to their level of kinship, and canonical scores were calculated using discriminant analysis and the x' and y' features. Of the 474 pairs of recorded maternal grandsire–grandson with both individuals genotyped, the probability for 28 pairs to belong to this level of kinship was low ( P  <   0.05), suggesting an error rate of around 3% per generation in pedigree determination.